Desenvolvimento inicial de Rhamdia branneri, Haseman, 1911 (Siluriformes: Heptapteridae), da Bacia do Rio Iguaçu - Lutz, Anelise Carradore (2013)
The catfish (Rhamdia branneri) is a native fish endemic to the Iguaçu River that has potential to grow due to their husbandry characteristics, due to this the present work aims to describe its initial development, with a view to commercial exploitation and management for conservation species. The study was conducted at the Experimental Station of Ichthyological Studies in Plant Ney Braga, reservoir Segredo, between January and February 2012. Spawnings were conducted, collected and analyzed 438 eggs, 394 individuals in the larval stage-yolk, 35 in pre-flexion, flexion 15 in, 13 in post-flexion and 1 juvenile. The eggs are yellow, non-adhesive and spherical, have a double membrane, diameter 1.13 mm, the perivitelline space has an average size of 0.21 mm during this period, there were four steps: initial cleavage, early embryo, and embryo free tail end. The larvae hatch after 26:00 hours at a temperature of 23.3 ° C, with mean standard length of 2.60 mm, are slightly pigmented and have a large yolk sac, being poorly developed. The complete absorption of the yolk sac occurs with 5.52 mm and exogenous feeding began with 39:00 hours, and can observe the presence of food in the digestive tract. It can be concluded that the characteristics of eggs, embryonic and larval development are essential for an understanding of the biology of R. branneri. Furthermore, the data constitute an information base for intensive species, and is considered of commercial interest and high potential for fish farming